Knowledge and experience regarding perioperative anaphylaxis among anesthesiologists in Istanbul - Gulben Yakarıca Ergen; Huseyin Erdogan; Filiz Dilek Sirinoğlu; Sibel Oba; Feyzullah Cetinkaya (AIMS Allergy and Immunology, 2017)
Anesthesiologists are among the physicians with the highest probability of encountering cases with anaphylaxis. Therefore, they should be familiar with recent developments in anaphylaxis diagnosis and treatment. This study assessed the personal experiences and knowledge of the current diagnostic criteria and management of anaphylaxis among anesthesiologists. Anesthesiologists working in Istanbul were randomly selected and requested to complete a 16-item questionnaire related to their experiences with perioperative anaphylaxis and knowledge about current anaphylaxis guidelines. The study group consisted of 203 physicians; 10.8% of them reported having experienced any case with perioperative anaphylaxis during their own practice. The leading responsible agents were penicillins and other antibiotics (36.3%), followed by neuromuscular blocking agents (32%). Most of the physicians reported hypotension as the most important sign of anaphylaxis under general anesthesia and preferred epinephrine as the first-line medication during anaphylaxis. Antibiotics and neuromuscular blocking agents were the most common causative agents identified in the cases of perioperative anaphylaxis experienced by our study group. Like other health care providers, anesthesiologists should be aware of recent advances in anaphylaxis diagnosis and treatment.